Allosteric Modulation of Muscarinic Receptors by Cholesterol, Neurosteroids and Neuroactive Steroids - Szczurowska, Ewa; Szánti-Pintér, Eszter; Randáková, Alena; Jakubík, Jan; Kudova, Eva (International journal of molecular sciences, 2022)
Muscarinic acetylcholine receptors are membrane receptors involved in many physiological processes. Malfunction of muscarinic signaling is a cause of various internal diseases, as well as psychiatric and neurologic conditions. Cholesterol, neurosteroids, neuroactive steroids, and steroid hormones are molecules of steroid origin that, besides having well-known genomic effects, also modulate membrane proteins including muscarinic acetylcholine receptors. Here, we review current knowledge on the allosteric modulation of muscarinic receptors by these steroids. We give a perspective on the research on the non-genomic effects of steroidal compounds on muscarinic receptors and drug development, with an aim to ultimately exploit such knowledge.
Keywords: Neurosteroids; Steroids; Cholesterol; Hormones; Receptors, Muscarinic; cholesterol; hormony; steroidy; receptory muskarinové; neurosteroids; neuroactive steroids; neurosteroidy; allosteric modulation; muscarinic receptors